Sex hormone binding globulin in Bangladeshi women with gestational diabetes mellitus - Tofail, Tania; Mohana, Choman Abdullah; Hasanat, Muhammad Abul (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Sex hormone-binding globulin (SHBG) is suppressed by hyperinsulinemia and insulin resistance. Aim: The aim of this study was to compare maternal SHBG levels between gestational diabetes mellitus (GDM) and normal glucose tolerant (NGT) women in our population. Methods: This study enrolled 42 women with GDM and 45 women with NGT screened by 75-gm 3-samples oral glucose tolerance test (OGTT) following WHO 2013 criterion for GDM. Plasma glucose was analyzed by the glucose oxidase method. Serum insulin levels were measured by the chemiluminescent immunoassay method. Quantitative determination of serum SHBG levels was done by immunochemiluminescent assay. Equations of homeostatic model assessment (HOMA) were used to calculate indices of insulin resistance (HOMA-IR), β-cell function (HOMA-B), and insulin sensitivity (HOMA-%S). Results: SHBG did not show any significant difference between the two groups (GDM vs. NGT: 795.74±122.01 vs. 718.73±50.67 nmol/L, p=0.55). There is no significant difference in trimester-wise SHBG concentration between NGT and GDM (p=0.370). Insulin resistance as measured by HOMA-IR (2.18±0.17 vs. 1.50±0.17, p <0.001) was significantly higher while insulin sensitivity HOMA-%S (61.99±6.05 vs. 134.53± 30.73, p <0.001) was significantly lower in GDM than those of NGT. Conclusion: There was no association between SHBG and glucose tolerance in this cross-sectional study of pregnant women. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2022; 1 (2): 39-43